Hemodialysis from basic research to clinical trials - Ronco, Claudio 1951-; Cruz, Dinna N. (Contributions to nephrology, 2008)
The field of hemodialysis is subject to constant transformations due to continuous advances in techniques, biomaterials and devices. Based on international surveys, objective evaluations of experts and recent clinical trials, the publication at hand pays special attention to the physiological aspects of treatments as well as practical questions in the dialysis unit. Taking into account recent developments, an international group of contributors addresses issues related to vascular access, epidemiology, inflammation, fluid management, uremic toxicity, treatment efficacy, advanced techniques, calcium/phosphate homeostasis, and correction of anemia.Focusing on basic and clinical aspects of innovative technology as well as on new therapeutic options, this publication is a most helpful tool for the clinician to keep abreast of developments in the field of hemodialysis